Repetition as artistic approach in Ukrainian fairy-tale of the 19th century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
At the present article the repetition was studied. The scientific studies were summarized. The classification of repetitions in Ukrainian linguistics was paid attention to. The types of repetitions in Ukrainian literary tales were presented as well. The scientific value is devoted to examples, author’s individual approach in using repetitions in texts of one plot.
Keywords: repetitions; types of repetitions; literary fairy-tale